2002
DOI: 10.1021/om020340o
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Complexes Containing Bis(diarylamido)/Thioether Ligands:  Synthesis and Their Catalysis for the Hydrogenation of Benzonitrile

Abstract: Treatment of the thioethers (RNH-o-C 6 H 4 ) 2 S (H 2 [R 2 NSN]; R ) Xy, Xyf; Xy ) 3,5-Me 2 C 6 H 3 , Xyf ) 3,5-(CF 3 ) 2 C 6 H 3 ) with 2 equiv of n-BuLi followed by addition of 0.5 equiv of [(η 6 -C 6 H 6 )-RuCl 2 ] 2 in THF gave the bis(diarylamido)/thioether complexes [(η 6 -C 6 H 6 )Ru[R 2 NSN]] (R ) Xy (1a), R ) Xyf (1b)) in moderate yields. In the presence of 1a (1 mol %) and PCy 3 (2 mol %; Cy ) cyclohexyl), benzonitrile was catalytically hydrogenated to give benzylamine (72%) and benzylidenebenzylamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 26 publications
0
55
0
Order By: Relevance
“…Cation 1 is obtained in 28 % yield and it can be isolated as the tetrafluoroborate salt (Scheme 1). The substitution of an η 6 -arene ligand at a ruthenium atom by three phosphane ligands has been observed so far for benzene, [4] toluene [5] and pcymene [6] ligands, but never for the strongly bound η 6 -C 6 Me 6 ligand. The single-crystal X-ray structure analysis of [1][BF 4 ], crystallised by slow diffusion of diethyl ether in a concentrated acetone solution of [1][BF 4 ], reveals for cation 1 the presence of three bridging hydrido ligands coordinated to the two ruthenium atoms, one ruthenium atom being coordinated to an η 6 -C 6 Me 6 ligand and the other one to three PMe 3 ligands.…”
Section: Resultsmentioning
confidence: 97%
“…Cation 1 is obtained in 28 % yield and it can be isolated as the tetrafluoroborate salt (Scheme 1). The substitution of an η 6 -arene ligand at a ruthenium atom by three phosphane ligands has been observed so far for benzene, [4] toluene [5] and pcymene [6] ligands, but never for the strongly bound η 6 -C 6 Me 6 ligand. The single-crystal X-ray structure analysis of [1][BF 4 ], crystallised by slow diffusion of diethyl ether in a concentrated acetone solution of [1][BF 4 ], reveals for cation 1 the presence of three bridging hydrido ligands coordinated to the two ruthenium atoms, one ruthenium atom being coordinated to an η 6 -C 6 Me 6 ligand and the other one to three PMe 3 ligands.…”
Section: Resultsmentioning
confidence: 97%
“…Takemoto et al [58] and Li et al [59] reported examples of homogeneous hydrogenation of nitriles into primary amines when alkoxide were added to ruthenium catalyst. Das et al [60] and Enthaler et al [61,62] also showed that addition of t BuOK and phosphine to simple ruthenium complex led to the fast hydrogenation of various nitriles and by replacing the phosphine ligand by a N-heterocyclic carbene, milder conditions could be operating [63].…”
Section: Tandem Alkene Metathesis / Hydrogenation Catalyses: From Plamentioning
confidence: 99%
“…[16] To improve the selectivity towards benzylamine, addition of an appropriate base was investigated. [15,17] Indeed, in the presence of potassium tert-butoxide, benzylamine is formed in good yield and with reasonable selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…[14] Notably, an improvement in the selectivity for the primary amine was reported by Hidai and co-workers by carrying out the reaction in the presence of catalytic amounts of base. [15] Nevertheless, with all of the above-mentioned catalyst systems, side products were formed in reasonable amounts thus lowering the selectivity towards primary amines and the overall atom efficiency. As shown in Scheme 1, the formation of secondary amines is caused by the reaction of the primary amine 3 with the imine intermediate 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation